2017
DOI: 10.1080/07900627.2017.1374930
|View full text |Cite
|
Sign up to set email alerts
|

Government facilitation of external initiatives: how Dutch water authorities cope with value dilemmas

Abstract: Water authorities search for new collaborations with nongovernmental actors, with the aim of facilitating societal initiatives. A comparative case study was conducted to analyze the value dilemmas faced by water authorities when they choose to facilitate and how they cope with these dilemmas. The study found that the most prevalent dilemma is between traditional democratic values and efficiency-related values. In the chosen solutions, the latter seem to prevail over the former. Casuistry, cycling and hybridiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 54 publications
(99 reference statements)
0
19
0
Order By: Relevance
“…In a participatory context, Verhoeven and Bochove (2018) recently showed that frontline workers in care and welfare services cooperating with volunteers, deal with tensions by moving away from frail volunteers and moving towards professional, vigorous volunteers. We encountered other ways of dealing with tensions in studies of public engagement processes, in particular co-production (Nils and Vogel 2018; Jaspers and Steen 2019), New Public Governance reforms (Van Gestel, Kuiper, and Hendrikx 2019; Sørensen and Bentzen 2020) and nongovernmental initiatives (Grotenbreg and Altamirano 2017). This also brought us to more recent work on dealing with value tensions in public policy (e.g.…”
Section: Dealing With Tensionsmentioning
confidence: 99%
“…In a participatory context, Verhoeven and Bochove (2018) recently showed that frontline workers in care and welfare services cooperating with volunteers, deal with tensions by moving away from frail volunteers and moving towards professional, vigorous volunteers. We encountered other ways of dealing with tensions in studies of public engagement processes, in particular co-production (Nils and Vogel 2018; Jaspers and Steen 2019), New Public Governance reforms (Van Gestel, Kuiper, and Hendrikx 2019; Sørensen and Bentzen 2020) and nongovernmental initiatives (Grotenbreg and Altamirano 2017). This also brought us to more recent work on dealing with value tensions in public policy (e.g.…”
Section: Dealing With Tensionsmentioning
confidence: 99%
“…In other words, water boards, by performing as a functional, mission-oriented government and simultaneously as a demand-oriented government, find it difficult to giving shape to ambidexterity or 'two-leggedness' (O'Reilly & Tushman, 2013). In a context that is primarily aimed at executing clearly defined tasks as cheaply as possible (Grotenbreg & Altamirano, 2017), it seems almost impossible to accommodate CBIs, aiming for a broader value creation than developing an infrastructure project alone. Having had a public monopoly on water-related tasks for centuries, the rise of CBIs can only be accommodated with institutional adaptation, making room for organizations other than public authorities to take action.…”
Section: Discussionmentioning
confidence: 99%
“…Van Buuren et al, 2015). Even more than in other countries, facilitating nongovernmental initiatives is innovative for Dutch water authorities compared with their traditional ways of working (Grotenbreg & Altamirano, 2017). Although other countries are generally more progressive in terms of granting nongovernmental actors an active role in the provision of public services, they are also searching for new forms of public-private collaboration and a more facilitative role for the government (Buser, 2013;Mees et al, 2016;Taylor, 2003).…”
Section: Conclusion and Discussionmentioning
confidence: 99%